Covid-19 and Mental Health Disorders in General: A Literature Review - Elzan Zulqad Maulana (HM Publisher, 2022)
In December 2019, there was an outbreak of a respiratory disease in Wuhan, China. The outbreak was initially reported from a viral infection attributed to Novel Coronavirus ended up classified as a SARS CoV-2. The symptoms from this virus were vary due to the ACE2 Receptor located in many organs of the body, but mostly in lung epithelial cells. The diseases were flu-like type but commonly developed into severe acute respiratory syndrome if the inflammation was occurred progressively. Numbers of hospital admission were significantly higher due to the patients with COVID-19 that needs to be isolated and treated. Up until now, the pandemic still haunts us and living besides us. Our society was overwhelmed by the viral infection, due to the new mutations and variants of the SARS CoV-2. There were mental health disturbances such as anxiety and major depression, traumatic events and moral injury that experienced by public and healthcare providers which affected by this pandemic. In this article we would like to evaluate overall mental health conditions of general society. Early recognition may improve better outcomes for our society, so we can overcome this pandemic without having any mental health disturbances. Developing effective strategies in order to manage COVID-19 related tasks as general public, especially healthcare providers.